2000
DOI: 10.1074/jbc.275.5.3247
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Characterization of Protein 4.1B, a Novel Member of the Protein 4.1 Family with High Level, Focal Expression in Brain

Abstract: The protein 4.1 family comprises a group of skeletal proteins structurally related to the erythroid membrane skeletal protein, 4.1R, that plays a critical role in determining the morphology and mechanical stability of the red cell plasma membrane. These proteins are characterized by the presence of three main conserved structural/functional domains. A 30-kDa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
134
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(145 citation statements)
references
References 55 publications
9
134
1
1
Order By: Relevance
“…Cultured astrocytes also expressed a 126-kDa Band 4.1B immunoreactive band (Fig. 4C); this molecular weight coincides with the size for Band 4.1B protein described in previous reports (12,13). The relative amount of Band 4.1B does not change in ␣v Ϫ/Ϫ astrocytes or neonatal brains (Fig.…”
Section: Band 41b Selectively Interacts With ␤8mentioning
confidence: 57%
See 1 more Smart Citation
“…Cultured astrocytes also expressed a 126-kDa Band 4.1B immunoreactive band (Fig. 4C); this molecular weight coincides with the size for Band 4.1B protein described in previous reports (12,13). The relative amount of Band 4.1B does not change in ␣v Ϫ/Ϫ astrocytes or neonatal brains (Fig.…”
Section: Band 41b Selectively Interacts With ␤8mentioning
confidence: 57%
“…A single clone identified from the Y2H library encoded Band 4.1B ( Fig. 1 C and D), a member of the Band 4.1 family of proteins (12,13). Mammalian Band 4.1 proteins contain three distinct functional domains: an N-terminal FERM domain, a central spectrin͞actin-binding domain, and a CTD (6,14,15).…”
Section: Band 41b Selectively Interacts With ␤8mentioning
confidence: 99%
“…Using an antibody that recognizes ezrin and crossreacts with radixin and moesin, these proteins were found to be present at high levels at the apical membranes in the virgin mammary gland (Figure 2a, arrow). We further found that ERM expression decreases dramatically during the proliferative stage of pregnancy and the differentiated stage of lactation before returning to high levels during late involution (Figure 2b- (Tran et al, 1999;Parra et al, 2000;Charboneau et al, 2002), we found that 4.1B also localizes to the membrane and cytoplasm in individual MDA-MB 436 cells, which do not form normal cell-cell contacts ( Figure 3b), and is concentrated at the tips of cell processes at apparent points of adhesion to the culture dish. Interestingly, 4.1B expression could be detected around and in the nuclei of these cells even though no such nuclear localization was apparent in mammary tissue sections.…”
Section: Erm Proteins Are Downregulated During Pregnancymentioning
confidence: 86%
“…All 4.1 family members are characterized by the presence of a conserved N-terminal membrane-association FERM (Fourpoint-one, Ezrin, Radixin, Moesin) domain (Chishti et al, 1998). In addition, most 4.1 proteins can associate with the spectrin-actin cytoskeleton by virtue of an actin-binding domain (Parra et al, 2000;Gimm et al, 2002). Both 4.1 and ERM proteins can act as structural proteins that link the plasma membrane to the actin cytoskeleton (Tsukita et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation